ESD-Oriented Project-Based Differentiated Learning Model to Develop Critical Thinking Skills and Biodiversity Literacy - Hetty Pratiwi; Endah Rita; Fenny Roshayanti; Siti Patonah (Universitas Pendidikan Mandalika, 2025)
The 21st-century learning must integrate learning models that are appropriate to students' needs in facing the challenges of the times. This study aims to develop a project-based differentiated learning model oriented to Education for Sustainable Development (ESD) to improve students' critical thinking skills and biodiversity literacy. This model was designed by integrating a differentiation approach, project-based learning, and sustainability values. Validation by experts showed that this model has a high level of relevance and integration, with an average score of 4.7 on a scale of 5. Implementation of the model on high school students showed a significant increase in critical thinking skills (18.5 points) and biodiversity literacy (17.7 points) based on the results of the pre-test and post-test. The success factors of this model include contextualization of materials, differentiation approaches, and integration of sustainability values. These results indicate that this model is effective and relevant to be applied in biodiversity learning in high schools. This study recommends further development with a wider population to ensure the sustainability of its impact. The implementation of this model should be accompanied by comprehensive training for teachers to ensure a deep understanding of the principles of differentiation, project-based learning, and ESD values.